Семантика і поетика роману «Золоті лисенята» Юліана Шпола - Гноєва, Н.І. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2008)
В статье анализируется один из экспериментальных романов 20-х годов XX века - «Золоті лисенята» Юлиана Шпола, его символика, особенности художественной структуры, роль автора, иронический дискурс.
The present article studies a 1920s experimental novel titled «Golden Fox Cubs» by Julian Shpol, revealing the novel's symbolism and artistical structure, the author's role and ironic discourse.
Keywords: романістика; експериментальний роман; композиційна деструкція; пародійний характер роману; експресивна емоційність